Impact of Climate Change on Marine Industry - S, Keshwini (Global journal of Business and Integral Security, 2024)
Sea level rise, coastal erosion, agricultural production, oil transportation interruptions, and maritime transportation are just a few of the many facets of climate change that this research explores. The study collected a substantial volume of data from a variety of sources and points of view by using a mixed-methods strategy that included quantitative and qualitative techniques. The maritime industry's stakeholders were surveyed and interviewed to provide primary data, which was supplemented by secondary data culled from literature reviews and previous studies. The study's findings, derived from a sample of 300 participants, provide insight into important demographic traits, perspectives, and worries concerned to the maritime sector. The bulk of the participants were men, ranging in age from 18 to 34. They had a minimum of a high school diploma and between 6 and 10 years of professional experience. The most numerous occupations were held by fishermen, who mostly held executive and managerial roles. A high degree of worry was found when analysing the respondents' knowledge of weather change concerns and their views on the danger that weather change poses to the maritime sector. The necessity for immediate action was highlighted by the fact that most respondents were aware of weather variation and saw it as a main danger to the maritime sector. Statistical tools, instances of statistical techniques include regression analysis and correlation testing, were used to thoroughly examine the study's hypotheses. The theories were supported by the outcomes, which look that the marine industry is significantly exaggerated by weather change, coastal erosion and accretion are affected by rising sea levels, agricultural production is affected by climate change, and maritime transportation is affected by interruptions in oil transportation. Eventually, the study emphasizes the critical significance of promptly tackling the complex issues that the maritime industry faces as a result of climate change. This report is great for scholars, politicians, and industry stakeholders since it lays out the complex interplay between environmental change and the maritime sector in detail. Protecting coastal populations, marine ecosystems, and maritime industries from the dangers caused by climate change requires effective adaptation and mitigation techniques